Small biochar particles added to coarse sandy subsoil greatly increase water retention and affect hydraulic conductivity - Bruun, E. W.; Ravenni, G.; Müller‐Stöver, D.; Petersen, C. T. (European journal of soil science, 2023)
Sandy soils can benefit greatly from the addition of biochar, but the benefits depend on the properties of both the soil and the biochar. This study investigated the role of biochar particle size in controlling pore size distribution, hydraulic conductivity and water retention after careful mixing with coarse sandy subsoil. Intact commercial pellets of straw biochar (SB; approx. 8 × 5 mm) and ground pellets separated into 6 size fractions (median diameter 15, 33, 44, 81, 135 and 205 μm) were investigated at two concentrations (1.50 and 3.00 wt%). The results were compared with effects obtained with another feedstock (wood; WB) and another soil. Light microscopy and water retention measurements showed that smaller biochar particles settled into large existing soil pores, creating smaller interstitial pores to a much greater extent than larger particles. Accordingly, small particles (≤44 μm) had large enhancing effects on water retention and hydraulic conductivity in the medium suction range (pF1.7‐pF3.0), which were not found to a similar extent after the addition of larger particles (>81 μm). It was not possible to systematically distinguish the effects obtained with the three smallest particle fractions (SB15, WB18 and SB33). All effects measured were greatest at the highest biochar concentration level. In one soil, amendment with 3.00 wt% of SB15 decreased the fractional volume of drainable pores with an equivalent diameter of ≥60 μm from 31.3 vol% in the control to 19.1 vol%, while increasing the volume of pores in the 0.2–60 μm range that could potentially retain plant‐available water from 8.7 vol% to 20.1 vol%. Hydraulic conductivity at pF1.7 was increased by a factor of 10 (from 2.3 to 22.5 cm/day) and at pF3.0 by a factor of 14 (from 0.1*10−3 to 1.4*10−3 cm/day). Similar effects were observed in the other soil but at slightly different levels. The PDI version of the bimodal van Genuchten model was successfully fitted to measured water retention and log‐transformed hydraulic conductivity data (RMSE values in the interval 0.0011–0.0029 and 0.024–0.215, respectively). Dynamic simulation under variable field conditions including the hydraulic properties of biochar‐amended soil layers could be a useful method to investigate the effects on crop water supply, water and fertilizer utilization and yields.